Quantifying thermal exposure for migratory riverine species: Phenology of Chinook salmon populations predicts thermal stress. (4th December 2020) - FitzGerald, Alyssa M.; John, Sara N.; Apgar, Travis M.; Mantua, Nathan J.; Martin, Benjamin T.
Abstract: Migratory species are particularly vulnerable to climate change because habitat throughout their entire migration cycle must be suitable for the species to persist. For migratory species in rivers, predicting climate change impacts is especially difficult because there is a lack of spatially continuous and seasonally varying stream temperature data, habitat conditions can vary for an individual throughout its life cycle, and vulnerability can vary by life stage and season. To predict thermal impacts on migratory riverine populations, we first expanded a spatial stream network model to predict mean monthly temperature for 465, 775 river km in the western U.S., and then applied simple yet plausible future stream temperature change scenarios. We then joined stream temperature predictions to 44, 396 spatial observations and life‐stage‐specific phenology (timing) for 26 ecotypes (i.e., geographically distinct population groups expressing one of the four distinct seasonal migration patterns) of Chinook salmon ( Oncorhynchus tshawytscha ), a phenotypically diverse anadromous salmonid that is ecologically and economically important but declining throughout its range. Thermal stress, assessed for each life stage and ecotype based on federal criteria, was influenced by migration timing rather than latitude, elevation, or migration distance such that sympatric ecotypes often showed differential thermal exposure. Early‐migration phenotypes were especially vulnerable due to prolonged residency in inland streams during the summer. We evaluated the thermal suitability of 31, 699 stream km which are currently blocked by dams to explore reintroduction above dams as an option to mitigate the negative effects of our warmer stream temperature scenarios. Our results showed that negative impacts of stream temperature warming can be offset for almost all ecotypes if formerly occupied habitat above dams is made available. Our approach of combining spatial distribution and phenology data with spatially explicit and temporally explicit temperature predictions enables researchers to examine thermal exposure of migrating populations that use seasonally varying habitats. Abstract : We evaluated thermal exposure and stress of Chinook salmon ( Oncorhynchus tshawytscha ) in their current freshwater range (i.e., below dams) and historically occupied habitat (i.e., above dams). Thermal stress was influenced by migration timing, such that sympatric ecotypes often showed differential thermal exposure. Fall‐runs were generally not thermally stressed, whereas spring‐runs showed high levels of thermal stress due to prolonged residency in streams during the summer. However, hope lies in the thousands of stream kilometers currently blocked by dams, where thermal stress would be substantially reduced or even eliminated for most ecotypes, even if stream temperatures warm by 2°C.